Black and sexy: a framework of racialized sexuality - Gilbert, Tracie Q. (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2022)
This book offers a unique understanding of African American populations and their articulation of sexuality and race by introducing a comprehensive sexological model, Black Sexual Epistemology. Tracie Q. Gilbert draws from theoretical perspectives of anti-Blackness, ethno-sexuality, Performative Blackness and African-centered epistemology to implicate race as an inextricable factor in the sexual structures and schema of African American people. Chapters identify and introduce a sex-positive and comprehensive sexological model, Black Sexual Epistemology, through which Black sexuality can be understood and navigated in the contemporary era. This model presents empirical data for effectively applying previous critical race perspectives and uniquely demonstrates how Black sexual experience can be better understood and reimagined for greater community development and healing. This book is essential reading for practicing sex therapists, marriage and family therapists and clinical social workers working with these populations as well as for academics and students of sexology, sex education, sex therapy, social work, marriage and family therapy, public health, Black/African American studies and LGBTQ studies. It will also be of interest to general audiences who appreciate culturally centered sexological scholarship.
Keywords: African Americans -- Sexual behavior; PSYCHOLOGY / Human Sexuality; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health